Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Wednesday, April 3, 2013 at 4:27pm.

Evaluate (f-g)(-3)

Then find (fg)(x)

Thanks a million

- college algebra -
**Steve**, Wednesday, April 3, 2013 at 4:43pm(fg)(x) = f(x)*g(x) = (x^2-3)(4x+1) = 4x^3 + x^2 - 12x - 3

(f-g)(-3) = f(-3)-g(-3) = 6-(-11) = 17

**Related Questions**

College algebra - Find the standard form of the equation of the hyperbola with ...

algebra - Evaluate T(x)=x^5-3x^4+4x+7 to find the exact value of T(-2.5)

math - i need some serious help with limits in pre-calc. here are a few ...

math - Find the derivative of the function and evaluate f '(x) at the given ...

math - Please need help on this Create an equation of a nonlinear function and ...

College Algebra - Find f(x-1) when f(x)=4x^2+5x+4

math - find thedomain and range of {(7,-2), (-6,-4) (9-9,)-(5-5)}= evaluate f(x...

college algebra - find all vertical and horizontal asymptoles f(x)=4x/x^+1

college algebra - given f(x)=4x-5, g(x)= x+5 over 4 Find (fog)(x). are these ...

college algebra - -4x^2y(-4x^3y^5)